The Reification of Value: Robust Realism and Alienation. Issue 3 (27th May 2021) - Compaijen, Rob; Meijer, Michiel
ABSTRACT: This paper explores the relation between metaethical reflection and value experience, and does so by focusing on robust realism. Robust realism is typically criticized for its ontological and epistemological commitments. In this paper, however, we hope to shed new critical light on the plausibility of the theory by using two concepts – 'reification' and 'alienation' – that have their origin in critical social theory. We use the concept of 'reification' as an interpretative lens to look at robust realism and show that it is reifying in two respects: it turns values into things, and, correspondingly, turns human agents into disengaged observers of those things. This analysis is then used to argue that robust realism is alienating in the sense that it distances us from the world that presents itself to us in value experience, and that it separates us from what we call our engaged responsiveness. We also argue that its alienating effects give us good reason to reject the theory.